The exchange eaudiobook - Grisham, John (The Firm, 2023)
#1 NEW YORK TIMES BESTSELLER • John Grisham delivers high-flying international suspense in a stunning legal thriller that marks the return of Mitch McDeere, the brilliant hero of The Firm. “A breathtaking update on the McDeeres and the life they made . . . Grisham, in vintage form, ratchets up the suspense in this winning sequel.” — The Wall Street Journal What became of Mitch and Abby McDeere after they exposed the crimes of Memphis law firm Bendini, Lambert & Locke and fled the country? The answer is found in The Exchange , the riveting sequel to The Firm , the blockbuster thriller that launched the career of America’s favorite storyteller. It is now fifteen years later, and Mitch and Abby are living in Manhattan, where Mitch is a partner at the largest law firm in the world. When a mentor in Rome asks him for a favor that will take him as far as Istanbul and Tripoli, Mitch finds himself at the center of a sinister plot that has worldwide implications. Once again Mitch’s colleagues, friends, and family are targeted. Mitch is a master at staying one staying one step ahead of his adversaries, but this time there’s nowhere to hide. Don’t miss Framed, John Grisham’s first work of nonfiction since The Innocent Man !